2015
DOI: 10.2351/1.4906389
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser melting of aluminum die-cast alloy—Correlations between process parameters, solidification conditions, and resulting mechanical properties

Abstract: Microstructure and property modifications of an AISI H13 (4Cr5MoSiV) steel induced by pulsed electron beam treatment J. Vac. Sci. Technol. A 28, 1349 (2010); 10.1116/1.3490019Effect of film thickness and laser energy density on the microstructure of a -GaAs films after excimer laser crystallizationThe additive production technology selective laser melting (SLM) is used for direct fabrication of metal-based functional components. SLM is one of the powder-bed based AM technologies. SLM is well established in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(72 citation statements)
references
References 9 publications
(8 reference statements)
5
66
0
1
Order By: Relevance
“…Susceptibility of the raw material to alterations caused by varying dwell times at the preheating temperature; variations in the thermal environment due to the transition from solid metal thermal environment to a powder-bed dominated environment Inhomogeneous microstructure and mechanical properties (hardness and strength) due to differing heat treatment stages and varying cooling rates; highly dependent on the material and the preheating settings [91,218,244] Azimuth angle (Θ)…”
Section: Surface Qualitymentioning
confidence: 99%
“…Susceptibility of the raw material to alterations caused by varying dwell times at the preheating temperature; variations in the thermal environment due to the transition from solid metal thermal environment to a powder-bed dominated environment Inhomogeneous microstructure and mechanical properties (hardness and strength) due to differing heat treatment stages and varying cooling rates; highly dependent on the material and the preheating settings [91,218,244] Azimuth angle (Θ)…”
Section: Surface Qualitymentioning
confidence: 99%
“…Stress-relieving heat treatment is recommended to eliminate these stresses. Heating the base plate also reduces the induced residual stresses significantly [18,19]. Microstructure of the resulting SLM part can be controlled by controlling the process parameters.…”
Section: Introductionmentioning
confidence: 98%
“…However, it was pointed out that the platform heating also has an important role on the LPBF consolidation phenomena and the microstructure evolution of the processed materials [23]. Buchbinder et al observed that during the LPBF process of AlSi10Mg, heating the building platform up to 220 • C causes the solidification of a different microstructure, lowering its mechanical properties [22].…”
Section: Introductionmentioning
confidence: 99%
“…One important building parameter is the building platform temperature which has an important effect on the microstructure and mechanical properties of LPBF parts [21][22][23]. In fact, most of the published studies used the platform heating mainly to reduce residual stresses in the part [21,24].…”
Section: Introductionmentioning
confidence: 99%